2021
DOI: 10.5530/ijper.55.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Exploration of Cyperus articulatus as a Potential Source of Nutraceuticals and Drug Ingredients

Abstract: Introduction: Cyperus articulatus rhizome has been used in folk medicine by different inhabitants belonging to tropical and subtropical regions. But its metabolite profile and potential pharmacological and food applications were hardly explored. Evaluation of biological activities of Cyperus articulatus metabolites was the objective of the present study. Materials and Methods: In vitro biological studies concerning radical scavenging, reducing activity, food (meat and β-carotene) protection, biomolecule (DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…To obtain pure ethanol for reuse, the ternary system technique required a substantial quantity of energy [ 37 , 38 ]. Previous studies reported that sequential extractions (from nonpolar to polar solvents) can improve the extraction efficiency and uncovering of widely phytochemical compounds and bioactivity [ 39 , 40 ]. However, the use of a wide variety of extraction solvents required proper waste management.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain pure ethanol for reuse, the ternary system technique required a substantial quantity of energy [ 37 , 38 ]. Previous studies reported that sequential extractions (from nonpolar to polar solvents) can improve the extraction efficiency and uncovering of widely phytochemical compounds and bioactivity [ 39 , 40 ]. However, the use of a wide variety of extraction solvents required proper waste management.…”
Section: Resultsmentioning
confidence: 99%
“…22 The essential oil of Cyperus articulatus was reported in various works of literature to have antimicrobial, anticancer, anticonvulsant and anti-malaria properties whereas the rhizome solvent extracts shown to have high antioxidant activities. [24][25][26][27] Potential α-glucosidase inhibition activity of the rhizome extract of Cyperus articulatus was studied by Swain and Hariprasad. 3 The dried rhizome was powdered and subjected to soxhlet extraction through a series of solvents in polarity order.…”
Section: Cyperus Articulatus Lmentioning
confidence: 99%